What can turtles teach us about the theory of ecological stoichiometry?. (6th January 2015) - Sterrett, Sean C.; Maerz, John C.; Katz, Rachel A.
Summary Vertebrate skeletons have high phosphorus (P) content relative to other tissues. Variation in skeletal investment within and among species is hypothesised to predict variation in P demand, standing stock and recycling. These relationships have been examined among fish, but not in vertebrates with more robust skeletons, such as turtles. Our objectives were to (i) describe freshwater turtle stoichiometry relative to skeletal mass, (ii) compare turtle body and excreta stoichiometry to patterns among fish and (iii) relate turtle skeletal stoichiometry to turtle nutrient storage and recycling. Skeleton constituted 82% of turtle dry mass. Total body %P increased ontogenetically with turtle mass and 93% of all P resided in the skeleton. Phosphorus storage within turtle assemblages was high (0.2–0.45 kg ha−1). Turtles excreted lower concentrations of P than fish. Excreta N:P was positively correlated with body N:P, suggesting that increased skeletal P investment was inversely related to P demand. Our results demonstrate that P stored in the bone of turtles can represent a large standing stock of P in fresh waters. Further, our work suggests skeletal investment alone is not sufficient to predict an animal's P demand and, by extension, their effects on nutrient recycling. Instead, our results indicate P demand is determined by both skeletal investment and growth rate. Consequently, taxa with high body P, extreme longevity and slow growth rates, such as adult turtles, may serve as stable standing stocks of nutrients while also contributing proportionately to nutrient remineralisation.